Proxy wars - Pavel V. Konyukhovskiy; Theocharis Grigoriadis (Freie Universität Berlin, School of Business & Economics, 2018)
Proxy wars are a key pattern of political conflict and interstate competition. Rather than resorting to direct conflicts, which are costly and entail a higher level of uncertainty, governments may opt for proxy wars, which may last longer, but are less costly and render them more immune to exogenous shocks. We start with the modeling of a direct war with two players where a static equilibrium may be neither realizable nor sustainable in the long run. Then, we offer a model of proxy war where the proposed equilibria are realizable, but not always sustainable in the long run. The consolidation level of the double principal-agent relationship predicts the continuation of conflict and thus the emergence of peace.
Keywords: C72; D72; D74; P51; 330; non-cooperative games; principal-agent models; proxy conflicts